Drivers of red fox (Vulpes vulpes) daily activity: prey availability, human disturbance or habitat structure?. (18th October 2015) - Díaz‐Ruiz, F.; Caro, J.; Delibes‐Mateos, M.; Arroyo, B.; Ferreras, P.
Abstract: Daily activity patterns in mammals depend on food availability, reproductive stage, habitat selection, intraspecific interactions and predation risk, among other factors. Some mammals exhibit behavioral plasticity in activity patterns, which allows them to adapt to environmental changes. A good example of this can be found in the red fox Vulpes vulpes . This species is adapted to living in highly humanized environments, where it is often culled because it may affect human interests (e.g. through the consumption of game species or livestock). We assessed the potential main drivers of the daily activity patterns of the red fox in 12 Iberian Mediterranean areas through the use of camera traps. Among drivers, we considered main prey availability (European wild rabbits Oryctolagus cuniculus ), degree of human disturbance (e.g. distance to human settlements, and intensity of predator control) and habitat structure. Our results revealed a predominantly crepuscular and nocturnal activity of foxes with local variations. Although overall fox activity increased with rabbit availability, the temporal overlap with prey activity was on average low, because foxes increased activity when rabbits decreased theirs (twilight‐night). Red fox activity rhythms seemed to be determined by human presence where human disturbance is high. In addition, diurnal activity decreased in areas with higher levels of human disturbance (closer to human settlements and high predator control intensity) and increased in dense habitats. Our study shows that daily activity patterns of highly adaptable species are determined by several interacting drivers, resulting in complex behavioral patterns. This suggests that further ecological studies should consider different factors simultaneously for a better understanding of daily activity patterns of wildlife in different landscapes.